2010
DOI: 10.1186/1471-2407-10-283
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of IL-8 and CXCR2gene polymorphisms on breast cancer susceptibility and aggressiveness

Abstract: BackgroundInterleukin-8 (IL-8/CXCL-8) is a prototype of the ELR+CXC chemokines that play an important role in the promotion and progression of many human cancers including breast cancer. We have recently showed the implication of polymorphism (-251) T/A of IL-8 gene in the susceptibility and prognosis of breast carcinoma. IL-8 acts through its CXCR1 and CXCR2 receptors. CXCR2, expressed on the endothelial cells, is the receptor involved in mediating the angiogenic effects of ELR+CXC chemokines and in particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 49 publications
3
75
0
1
Order By: Relevance
“…The CXCR2 TC genotype was found to be more abundant, suggesting that patients in the Limpopo Province primarily carry the heterozygous TC genotype compared to other homozygous genotypes. However, different results obtained by Snoussi et al (2010) suggested that the CC genotype was the predominant genotype among the Tunisian population. These authors also found a highly significant association between the homozygous CXCR2 (+ 1208) TT genotype and breast carcinoma in terms of frequency, but also found a significant association with an aggressive phenotype of breast carcinoma as defined by large tumor size, high histological grade, and auxiliary lymph node metastasis (Snoussi et al, 2010).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The CXCR2 TC genotype was found to be more abundant, suggesting that patients in the Limpopo Province primarily carry the heterozygous TC genotype compared to other homozygous genotypes. However, different results obtained by Snoussi et al (2010) suggested that the CC genotype was the predominant genotype among the Tunisian population. These authors also found a highly significant association between the homozygous CXCR2 (+ 1208) TT genotype and breast carcinoma in terms of frequency, but also found a significant association with an aggressive phenotype of breast carcinoma as defined by large tumor size, high histological grade, and auxiliary lymph node metastasis (Snoussi et al, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…CXCR2 and its chemokine ligands genotypes are involved in a wide range of acute and chronic inflammatory diseases, including acute respiratory distress syndrome (Kurdowska et al, 2002), rheumatoid arthritis (Erdem et al, 2005;Lally et al, 2005), psoriasis (Reich et al, 2001), inflammatory bowel disease (Banks et al, 2003), chronic obstructive pulmonary disease and asthma (Keatings et al, 1996;Beeh et al, 2003;Chapman et al, 2009), aggressive cancer (Snoussi et al, 2010), cystic fibrosis (Koller et al, 1997), and atherosclerosis (Bizzarri et al, 2006). However, whether different genotypes of the genes coding for these cytokines are involved in the susceptibility to opportunistic infections among HIV patients is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primers used were 5'-CTAGAAATAAAAAAGCATACAA-3'; (-251A) 5'-CTAGAAATAAAAAAGCATACAT-3' (-251T); and the common primer 5'-AATACGGAGT ATGACGAAA-3'. These primers yielded a PCR product of about 200 bp, as described by Snoussi et al (2010). AS-PCR cycling conditions were as follows: predenaturation at 96°C for 10 min, a touchdown procedure of 25 s at 95°C followed by annealing for 45 s at temperatures decreasing from 55°C (four cycles) to 50°C (25 cycles), and elongation at 72°C for 40 s. PCR products were stored at 10°C.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…Biomedical and genetic studies have shown the effects of IL-8 gene polymorphisms in the pathogenesis of chronic inflammatory diseases, such as cancer (Snoussi et al, 2010), tuberculosis (TB) (Otsuka et al, 2005), and other infections. Nevertheless, no studies have investigated the effects of IL-8 on OIs in HIV patients.…”
Section: Introductionmentioning
confidence: 99%